2013
DOI: 10.1111/ajt.12401
|View full text |Cite
|
Sign up to set email alerts
|

What Is the Impact of Hypogammaglobulinemia on the Rate of Infections and Survival in Solid Organ Transplantation? A Meta-Analysis

Abstract: Hypogammaglobulinemia has been described after solid organ transplantation and has been associated with increased risk of infections. The aim of the study was to evaluate the rate of severe hypogammaglobulinemia and its relationship with the risk of infections during the first year posttransplantation. Eighteen studies (1756 patients) that evaluated hypogammaglobulinemia and posttransplant infections were included. The data were pooled using the DerSimonian and Laird random-effects model. Q statistic method wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
151
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(163 citation statements)
references
References 39 publications
9
151
1
2
Order By: Relevance
“…4,7 Additionally, Florescu and associates revealed in their study that donor CMV strain more frequently causes CMV infection than the recipient virus. 9 An earlier study by Gane and associates revealed similar results as our study: D+/R+ patients receiving a CMV prophylaxis with ganciclovir for 3 months developed significantly less CMV disease (2.6% vs 18.2%, P = .002). 10 Atabani and associates included patients after liver transplant (n = 374) and kidney transplant (n = 497) who received a preemptive therapy.…”
Section: Discussionsupporting
confidence: 90%
“…4,7 Additionally, Florescu and associates revealed in their study that donor CMV strain more frequently causes CMV infection than the recipient virus. 9 An earlier study by Gane and associates revealed similar results as our study: D+/R+ patients receiving a CMV prophylaxis with ganciclovir for 3 months developed significantly less CMV disease (2.6% vs 18.2%, P = .002). 10 Atabani and associates included patients after liver transplant (n = 374) and kidney transplant (n = 497) who received a preemptive therapy.…”
Section: Discussionsupporting
confidence: 90%
“…Nevertheless, a recent meta-analysis reported that mild (serum immunoglobulin G (IgG) levels 400–700 mg dl −1 ) and severe (IgG <400 mg dl −1 ) HGG occur in as many as 39% and 15% of patients during the first year post-transplant, respectively. 11 The incidence and clinical implications of HGG have been assessed in kidney, 12, 13, 14, 15 liver, 16 lung, 17, 18, 19 heart 20 and intestinal 21 transplant recipients. The mechanisms leading to post-transplant HGG are not fully clarified and are likely multifactorial, including the decrease in CD4 + T-cell numbers and its subsequent impact on B-cell activation.…”
Section: Non-pathogen-specific Monitoringmentioning
confidence: 99%
“…[6][7][8] This conforms with the general observation that diminished overall humoral immunity, as indicated by a low IgG level (hypogammaglobulinemia) either before or after transplant, has been shown to increase the risk of CMV infection in SOT recipients. 7,16 Therefore, lower CMVspecific humoral immunity appears to predispose patients to a higher risk of posttransplant CMV infection. Anecdotally, CMV-Ig is being used as an adjunctive treatment for severe cases of CMV disease, especially pneumonitis and recurrent CMV disease, and for recipients with severe hypogammaglobulinemia.…”
Section: Discussionmentioning
confidence: 99%
“…19,20 A previous study found that superinfection with a donor CMV strain virus may occur more frequently in comparison with endogenous reactivation from the recipient virus in kidney transplant recipients. 16 In order to investigate the impact of the donor CMV titer and the risk of CMV infection, those with available donor CMV antibody titers were analyzed. However, there was no significant association between donor CMV antibody titers and posttransplant CMV infection in our study.…”
Section: Discussionmentioning
confidence: 99%